Spondylodiscitis and ankylosing spondylitis: HLA typing and nosological implications. Issue 6 (December 1978) - Modena, V; Migone, N; Daneo, V; Carbonara, A O; di Vittorio, S; Viara, M
Abstract : Nine cases from among 64 patients with ankylosing spondylitis (AS) are described. In addition to bilateral sacroiliitis these cases had a peculiar type of spondylodiscitis characterised by quite diffuse and marked sclerosis of multiple vertebral bodies, with only minimal erosions of the adjacent vertebral plates while classical syndesmophytosis was absent. The antigen HLA-B27 was found only in 1 of these 9 cases. This type of spondylodiscitis could discriminate among all the patients with AS a subgroup with a peculiar clinical pattern and a probably distinctive pathological mechanism.